Successful Outcome of Pregnancy in two Cases of Takayasu Arteritis - Rashid, Fahmida; Jamil, Mohammed Safayet; Das, Durjoy; Abedin, Saiyed Mohammad Minhajul; Chowdhury, Fahmida Islam; Alam, Muhammad Khurshed; Akter, Shahena; Sattar, Mohammad Abdus (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Introduction : Takayasu arteritis is a vasculitis of unknown cause. It is a disease of involvement of vessels of branches of the aortic arch. It can affect women of reproductive age and may present with pregnancy. Pregnancy may have a favorable outcome if diagnosed and appropriately managed from the onset of the disease and enter pregnancy in the remission phase and with medication. But, if it is diagnosed for the first time during pregnancy outcome might be worse. Case reports: Here presented two case reports of diagnosed Takahashi Arteritis with term pregnancy; who entered pregnancy in remission phase and on medication. The prior preparation leads the pregnancy to a successful outcome without any residual effect on feto-maternal health. Conclusion: Early diagnosis of the disease and proper management of the progress of the disease by intervention is essential for a good prognosis. A close follow-up and multidisciplinary approach during pregnancy make pregnancy a safer journey for a woman with Takahashi Arteritis. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(1): 63-67